Profitability of banking in the negative interest rate era : the relevance of ownership structure and loan portfolio quality - Viljanen, Evita (2022)
Negative money market interest rates have been a defining feature of European economy during the years 2015-2022, which can be called as a negative interest rate era. On top of the aggregate economy, this era has also influenced the banking sector and the banking business. The topic of this master’s thesis is to find out the most significant variables that have influenced on the profitability of banking sector. Variables defining the profitability are especially researched through the perspective of bank’s size, ownership structure and the locale of the bank meaning if it situates in the Euro area or outside of it. One key standpoint of this thesis is the effect of loan portfolio quality to the bank’s profitability. This thesis was conducted as quantitative research using various panel econometric techniques. The data included over 560 banks from 35 different European countries. Three different variables were used to measure the profitability: return on average assets (ROAA), return on risk weighted assets (RoRWA) and net interest margin (NIM). The main result involving the effect of the loan portfolio quality indicate that for the shareholder owned banks in the Euro area and co-operative and savings banks outside the Euro area it could even be beneficial to increase the loan portfolio riskiness, as for these banks the increasing share of non-performing loans is recorded to have positive effect on ROAA. One explanation to this is that these banks can match the recognized risk with appropriate pricing. However, the increase in the riskiness of the loan portfolio could not be suggested for the shareholder owned banks outside the Euro area as for those banks the perceived profitability is worsened though increased share of non-performing loans. The results indicate that banks with different characteristics are affected by different independent variables. It is also recorded, that the same independent variable can cause an impact that is negative for some banks and positive to another. As an example for variation within the results, the faster growth speed of a shareholder owned bank is recorded to cause harm on NIM but benefit the broader profitability measure ROAA. Because of these notions it is important that each bank makes the practical decisions through their own perspective, rather than solely relying on theory or following the example set by the other banks.